The GAMBARAN RISIKO DEKUBITUS PADA PENDERITA STROKE DI WILAYAH KERJA RSUD DR.H.SLAMET MARTODIRDJO PAMEKASAN : GAMBARAN RISIKO DEKUBITUS PADA PENDERITA STROKE DI WILAYAH KERJA RSUD DR.H.SLAMET MARTODIRDJO PAMEKASAN - Syakura, Abdan (Jurnal Sains dan Teknologi Kesehatan, 2021)
Abstrack: Introduction: Stroke is a disease that requires the help of tools or other people to carry out activities, if this is allowed to continue, there is a risk of decubitus events. The purpose of this study was to describe the risk of pressure sores in stroke patients. Methods: The design used in this scientific paper uses a descriptive cross sectional design because it describes the risk of pressure sores in stroke patients. Respondents were 40 people in the working area of ??RSUD Dr. H. Slamet Martodirdjo Pamekasan. The technique used is non-probability purposive sampling, in this study focused on stroke patients. Data collection was carried out on February 4, 2021 by providing a closed-ended-multiple choice questionnaire using the Norton scale type containing 5 question items. Results: most of the respondents as many as 25 people (63%) were at low risk for the incidence of pressure sores. Conclusion: Stroke sufferers are able to choose a bed, bed or wheelchair with materials that are safe and used so that they can reduce or prevent the risk of pressure sores. Key words: Stroke, Decubitus. activity